Exploring the Role of HR Intervention Programs in Reducing the Impact of Toxic Leadership on Employee Switching Intentions - Indra Pratama; Kholid Ansori (Nomico, 2025)
Toxic leadership is a phenomenon that has a serious impact on the psychological well-being of employees and increases the intention to change jobs. To answer this challenge, this study aims to analyze the role of HR intervention programs in mitigating the impact of toxic leadership on turnover intention. The study used a quantitative approach with a survey design, involving 300 respondents from various departments and departments in organizations that had implemented HR intervention programs. Data were collected through a Likert scale-based questionnaire and analyzed using multiple regression and bootstrap mediation tests. The results showed that toxic leadership had a significant positive effect on job transfer intention (β = 0.52; p < 0.001). In contrast, HR intervention programs had a significant negative effect on job transfer intention (β = –0.33; p < 0.01), with a model contribution of R² = 0.47. Furthermore, HR programs have been shown to partially mediate the relationship between toxic leadership and conversion intentions, so that while direct influence remains, the impact can be suppressed through HR mechanisms. In conclusion, HR interventions play an important role in increasing employee retention, but their effectiveness will be optimal when accompanied by leadership behavior transformation. These findings confirm that HR is not only administrative, but also strategic in maintaining organizational sustainability.